Distribusi dan Karakteristik Kepiting Bakau (Scylla spp.) di Kawasan Rehabilitasi Mangrove Pantai Sei Tuan Indah Kecamatan Pantai Labu Kabupaten Deli Serdang - ahmad zulfani, ahmad zulfani; Fadhilah, Amanatul; Susetya, Ipanna Enggar; Yusni, Eri (Talenta Publisher, 2022)
Research on the distribution and characteristics of mangrove crabs (Scylla spp.) in the Sei Tuan Indah Beach, Pantai Labu District, Deli Serdang Regency's mangrove rehabilitation area has been carried out from August to September 2021. This study aimed to determine the distribution and characteristics of mangrove crabs in the mangrove rehabilitation area of Sei Tuan Indah Beach, Pantai Labu District, Deli Serdang Regency, North Sumatra Province. The method used in this research is the line transect method and the Line Transect point method for measuring mangrove data and catching mangrove crabs using traditional fishing gear, namely Bubu. The results of the study obtained a total sample of 80 crabs in 3 types, namely: Scylla olivacea, Scylla tranquebarica, and Scylla paramamosain with the most dominant sex being male. The study's results obtained a pattern of distribution of mangrove crabs with a value of Id = 2.5. Analysis of correlation between environment, water parameters, and distribution using Principal Component Analysis (PCA)